Movingparts - Carson, Edward, 1948- (Hugh MacLennan poetry series., 2023)
"In Edward Carson's provocative new work, the poetic moving parts of movingparts confront and breathe new life into what's true and what's not in Aesop's fable The Fox and the Crow, as well as the shifting, often fragmentary ground between what's said and what's not about identity and intimacy in Sappho's lyrics. Reflecting the moment-to-moment ways our minds think, these poems take us from a creative process of disconnection and reassembly to a sonic pacing of words arising out of their stillness on the page. A flair for syntactical compression is found throughout, balanced by a capricious yet transforming diction, what John Ashbery described as seeking to stretch "the bond between language and communication." Calling witness to the narratives of history while pivoting their reach forward to the present, the rhythms, allusions, and resulting outcomes of Carson's use of language expand both narrative and discovery. movingparts is brought full circle when an unexpected historical connection between Sappho and Aesop is revealed, and that what is true and/or false in the past or present of our lives can arrive at an intimacy with and illumination of more than we imagine."--